This Changes Everything The Sixth Extinction and its Implications for Pastoral Theology - LaMothe, Ryan 1955- (2016)
In this article, I consider how climate change and its current and future calamities might alter pastoral theology. I then ask how pastoral theology as a guild and discipline might change given the realities of the Anthropocene Age. More particularly, I address three areas of pastoral theology vis-à-vis change, namely research, teaching, and the guild's organization (Society for Pastoral Theology). The aim is not to be prescriptive, but to invite discussion about this key issue for humanity.
Keywords: Climate Change; Care; Pastoral Theology; Politics; Suffering